Considering and Making the Best Possible Future from an Educational Standpoint - Galli, Marianna (2015)
The interview with Dr. Horacio Ademar Ferreyra allows us to access the field of educational policies from a point of view that combines academic knowledge with political decision, school practices, and reflections on them.  On this horizon, it becomes indispensable to approach schools in a particular context, in accordance with the different social problems.  In this sense, the legislation in effect becomes the starting point to rethink the challenge of having quality and inclusion in education. Emphasizing the development of citizenship, the interviewee proposes, from his own experience, the defining features of a quality school when redefining the subjects involved and their practices in and from the school.